Üsküdar Kadısı Ali Nureddin Yüce ve Kasîde fî Esmâi's-Süver Tercümesi - (:unkn) unknown (My University, 2013)
Arapların Müslümanlığı kabulünden sonra, asırlardır önemli bir gelenek olarak yaşattıkları şiirin muhtevâsında bazı değişiklikler olmuştur. Hz. Peygamber devrinden başlayıp günümüze kadar gelen peygamber methiyeleri, İslam ile beraber Arap şiirinin önemli bir nazım türü haline gelmiştir. Söz konusu methiyelerden biri de İbn Câbir el-Endelüsî'nin her beyitte Kur'ân-ı Kerîm sûrelerinin adlarını telmîh yoluyla verdiği kasîdesidir. Son devir Osmanlı âlimlerinden Üsküdar Kadısı Ali Nureddin Efendi bu kasîdeyi Türkçeye çevirmiş ve Cevâhiru'z-zevâhir adlı eserinin içerisinde neşretmiştir. Bu makalede Ali Nureddin Efendi'nin hayatı anlatılıp eserleri tanıtılacak, ardından mezkûr tercümesinin çeviriyazımı verilecektir.

The contents of Arabian poems, which had kept its existance for centuries, changed to a certain extent after the Arabs embraced Islam. The panegyric odes of the prophet, that started in his day and continued to modern-day, became an important genre of prose in the Arabian poetry with Islam. One of these odes is Ibn Caber al-Andalusi's qasidah, which makes references to the names of Quranic suras in each couplet. Ali Nureddin, the judge of Uskudar, who lived in the last period of the Ottoman State, translated and published this qasidah in his book Cevâhiru'z-zevâhir. This article analyzies Ali Nureddin's life and works, followed by the translation of the said qasidah.
Uskudar's Judge Ali Nureddin Yuce and His Translation of "Qasidah fi Asmâ Al-Suver"
Keywords: Din Bilimi